Pembentukan Karakter Religius Bagi Peserta Didik Melalui Organisasi IPNU IPPNU di MA Babussalam Mojoagung Jombang - A. Syafi' AS.; Eko Hadi Wardoyo; Rodotul Jannah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This study aims to determine how the process of religious character formation for students through the IPNU-IPPNU organization and what are the benefits of IPNU-IPPNU activities for students of MA Babussalam Mojoagung Jombang. This type of research is field research using a qualitative approach with a case study type. The subjects in this study were the principal, IPNU-IPPNU mentor teachers, IPNU chairman, IPPNU chairman, and IPNU-IPPNU members of MA Babussalam Moljoagung Jombang. Data collection techniques through observation, interviews and documentation. After the data was collected and analyzed using the Miles and Huberman Triangulation model technique, data reduction, data presentation, and drawing conclusions or verification. This study succeeded in obtaining findings, namely the formation of religious character of students through the IPNU-IPPNU MA Babussalam organization is considered to be optimal. The process of forming religious character is carried out through collaboration between the IPNU-IPPNU organization and through the work programs that are made. Other programs/efforts carried out by schools in instilling religious character education in students are to get used to praying at the beginning and end of learning, pilgrimage, istighosah, tahlil, khatmil Al Qu'an and so on. Keywords: Religious Character, IPNU-IPPNU Organization